The regulations for the assurance of the reliability of pressure vessels - Vitez, Ivan (Materiali in tehnologije, 2000)
In this article the most important differences in the regulations for the assurance of the reliability of pressure vessels in some developed countries of the world (USA, Germany, Britain and France) are considered. Using a comparison of these regulations a common basis is given regarding the possible severe consequences in the case of failures. Establishing quality assurance is necessary for the high reliability of pressure vessels.
Keywords: tlačne posode; predpisi; kvaliteta; zanesljivost